RHEOLOGICAL CHARACTERISTICS OF ORAL GELS WITH INCORPORATED MEDICINAL PLANT EXTRACTS - Katona, Gabor; Kalić, Marina; Vojvodić, Slađana; Panjković, Katarina (Archives of Pharmacy, 2023)
For patients suffering from teeth and gum diseases 21st-century pharmacy provides growing array of treatment possibilities. While these diseases result from inflammation of dysbiotic origin, development of resistance restricts the effectiveness of available medicinal substances. An alternative solution could be plant extracts with anti-inflammatory and antimicrobial effects. This research aimed to examine how plant extracts can affect the rheological properties of basic oral gel formulation. Three preparations of identical compositions containing different lyophilized aqueous plant extracts Thymus vulgaris L., Ocimum basilicum L. and Lavanda angustifolia Mill. were formulated. Gels were prepared using 0,5% Carbomer 940 as gelling agent and 1% of plant extract, with homogenization (DLAB Scientific, China; 160W AC carbon brush motor) during 2 minutes at 30.000 spins. Rheological tests were performed using Haake MARS rheometer (Thermo Scientific, Karlsruhe, Germany) using a Z20 DIN cylinder measuring instrument at 22±0,1°C. Flow curves were examined using the hysteresis procedure. Based on the obtained results, values of apparent viscosities were gathered at the maximum shear rate of 50s-1. The lowest apparent viscosity showed gel with basil extract, while the highest showed gel with lavender extract. Since it has been demonstrated that the choice of plant extract has impact on rheological characteristics of prepared formulations, future research should focus on investigating causes of such results, as well as appropriate selection of plant extracts during formulation, considering not only therapeutic but also technological parameters.